Silver(i)-catalyzed novel ipso-cycloaddition and retro-Friedel–Crafts reaction of ortho-hydroxyphenyl-substituted para-quinone methides. Issue 22 (30th September 2021) - Zhuo, Caiqi; Song, Ran; Liu, Zhanxu; Xiang, Qirui; Yang, Daoshan; Si, Wen; Lv, Jian
Abstract : The Lewis acid AgPF6 was found to catalyze novel [2 + 2] ipso -cycloaddition and retro-Friedel–Crafts reaction of o -hydroxyphenyl-substituted p -quinone methides in the presence of H2 O, affording the polysubstituted triarylmethanes in up to 97% yields. Abstract : The Lewis acid AgPF6 was found to catalyze novel [2 + 2] ipso -cycloaddition and retro-Friedel–Crafts reaction of ortho -hydroxyphenyl-substituted para -quinone methides in the presence of H2 O (1 equiv.) effectively, affording the polysubstituted triarylmethanes in up to 97% yields.